Thrifting Crisis Communication: A Smart Response to Import Bans and Sluggish Sales - Nila Nurlimah; Indriyati Kamil; Retna Sari (Journal of Creative Power and Ambition (JCPA), 2026)
The increase in thrift product prices at Cimol Gedebage Market in Bandung has created a negative perception among consumers, which has then developed into negative Word of Mouth (WOM) both on social media and in person. This situation has forced thrift merchants to respond strategically to maintain the sustainability of their businesses. This study aims to analyze the crisis communication strategies employed by thrift merchants at Cimol Gedebage Market in responding to perceptions of high prices. The study uses a qualitative method with data collection techniques including observation, in-depth interviews with merchants, buyers, and market managers. The results show that vendors implement crisis communication strategies aligned with the Situational Crisis Communication Theory (SCCT), including excuse and justification strategies. Additionally, persuasive approaches such as offering discounts, explaining product value, and engaging in bargaining interactions with customers contribute to the creation of positive word-of-mouth (WOM) as a form of perception recovery. This study is expected to contribute theoretically to the development of crisis communication literature in the informal sector, particularly in the thrifting business, and serve as a practical reference for business operators and policymakers in formulating effective communication strategies to address crisis-based challenges in the informal sector.